Clinical Features, Prognostic Factors, and Treatment Interventions for Ulceration in Patients With Infantile Hemangioma - Fernández Faith, Esteban (JAMA Dermatol, 2021)
IMPORTANCE: Ulceration is a common complication of infantile hemangioma (IH), which leads to substantial morbidity. Ulceration in IH has not been systematically studied since the advent of β-blocker therapy for IH. OBJECTIVES: To examine treatment interventions used for ulceration in IH and identify clinical prognostic indicators of healing time. DESIGN, SETTING, AND PARTICIPANTS: A retrospective, multicenter cohort study was conducted on 436 consecutive patients with a clinical diagnosis of ulcerated IH and available clinical photographs. Patients receiving care at tertiary referral centers evaluated between 2012 and 2016 were included; statistical and data analysis were performed from February 7 to April 27, 2020. EXPOSURES: Clinical characteristics, treatment interventions, course, complications, and resource use were analyzed. Treatment interventions for ulceration in IH included local (wound care, topical), systemic (β-blocker, corticosteroids), and procedural (pulsed-dye laser). MAIN OUTCOMES AND MEASURES: The primary end point was time to complete or nearly complete ulceration healing. Clinical characteristics were analyzed to determine the responses to most common interventions and prognostic factors for healing of ulceration. RESULTS: Of the 436 patients included in the study, 327 were girls (75.0%); median age at ulceration was 13.7 weeks (interquartile range, 8.86-21.30 weeks). The median heal time was 4.79 weeks (95% CI, 3.71-5.86 weeks) with wound care alone, 5.14 weeks (95% CI, 4.57-6.00 weeks) with timolol, 6.36 weeks (95% CI, 5.57-8.00 weeks) with a systemic β-blocker, and 7.71 weeks (95% CI, 6.71-10.14 weeks) with multimodal therapy. After adjusting for IH size, a dose of propranolol less than or equal to 1 mg/kg/d was associated with shorter healing time compared with higher propranolol doses (hazard ratio, 2.04; 95% CI, 1.11 to 3.73; P = .02). Size of the IH was identified as a significant prognostic factor for healing time in multivariable analysis. Increasing size of IH portends a proportionately longer time to heal of the ulceration. CONCLUSIONS AND RELEVANCE: Despite the use of β-blockers, this cohort study found that a subset of patients with IH ulceration continued to experience prolonged IH healing times. Larger IH size appears to be a poor prognostic factor for time to heal. For patients requiring systemic therapy, initiation of propranolol at lower doses (≤1 mg/kg/d) should be considered.